2018
DOI: 10.1029/2017jd027992
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Caveats of Weighting Climate Models for Summer Maximum Temperature Projections Over North America

Abstract: Uncertainties in climate projections exist due to natural variability, scenario uncertainty, and model uncertainty. It has been argued that model uncertainty can be decreased by giving more weight to those models in multimodel ensembles that are more skillful and realistic for a specific process or application. In addition, some models in multimodel ensembles are not independent. We use a weighting approach proposed recently that takes into account both model performance and interdependence and apply it to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
149
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 63 publications
2
149
0
Order By: Relevance
“…Weights are calculated for each model following the approach presented by Lorenz et al (2018), which is based on earlier work from Knutti et al (2017) and Sanderson et al (2015aSanderson et al ( , 2015b. Each weight w i is a combination of the observational distance D i (informing the performance weighting) and the model distance S ij (informing the independence weighting):…”
Section: Model Weightingmentioning
confidence: 99%
See 3 more Smart Citations
“…Weights are calculated for each model following the approach presented by Lorenz et al (2018), which is based on earlier work from Knutti et al (2017) and Sanderson et al (2015aSanderson et al ( , 2015b. Each weight w i is a combination of the observational distance D i (informing the performance weighting) and the model distance S ij (informing the independence weighting):…”
Section: Model Weightingmentioning
confidence: 99%
“…The shape parameters define the strength of the weighting and the relative importance of performance and independence, large values will lead to an approximation of equal weighting, while small values will lead to aggressive weighting, giving a few models most of the weight. The shape parameters used in this study are summarized in table 1 and their calculation is described by Lorenz et al (2018) and in the supplement.…”
Section: Model Weightingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although internal variability has been shown to influence trends in water availability for 20-year periods (Kumar et al, 2015), Greve et al (2018) found that model uncertainty is dominating the spread of projected changes in long-term water availability. Moreover, Lorenz et al (2018) highlight that model uncertainty is ©2018. The Authors.…”
Section: Introductionmentioning
confidence: 99%